(untitled) (International Journal of Food and Nutritional Sciences, 2023)
In today’s dynamic marketing setting, the influence of social media on consumer behavior is a critical area of study, particularly in cities like Bengaluru, India’s Silicon Valley. This research explores how social media advertisements shape consumer behavior in Bengaluru, considering the city’s diverse demographic composition and tech-literate population. The study employs a quantitative approach, gathering data from 80 respondents through structured questionnaire by Penrose Karwitha Mwiti (2020) to analyze the impact of social media advertisements on consumer perceptions, attitudes and purchasing decisions. The findings reveal that social media platforms such as Facebook, Instagram, Twitter and YouTube are deeply integrated into the daily lives of Bengaluru residents, influencing consumer behaviors through targeted reach and engaging content. Key insights include the effectiveness of social media in defining target markets, enhancing consumer insights and fostering consumer engagement. Moreover, demographic factors like educational qualifications significantly influence how individuals perceive and respond to social media advertisements, highlighting the importance of tailored marketing strategies. This study contributes to the literature by providing empirical evidence of social media’s role in influencing consumer behavior within Bengaluru’s unique market context. It offers actionable recommendations for marketers to enhance advertising effectiveness, engage diverse consumer segments and strengthen brand perception in a competitive urban environment.